Risk of Incident Atrial Fibrillation and Subsequent Use of Oral Anticoagulants in Patients with Dementia - Tsai, Chuan-Tsai; Chan, Yi-Hsin; Liao, Jo-Nan; Chen, Tzeng-Ji; Lip, Gregory Y. H.; Chen, Shih-Ann; Chao, Tze-Fan (Thrombosis and Haemostasis, 2023)
Background Dementia and atrial fibrillation (AF) have many shared risk factors. Besides, patients with dementia are under-represented in randomized trials, and even if AF is present, oral anticoagulants (OACs) are not prescribed frequently. This study aimed to report the incidence of newly diagnosed AF in dementia patients, and the impacts of use of vitamin K antagonist (VKA; e.g., warfarin) and non-VKA OAC (NOACs) on stroke and bleeding outcomes.Methods Our study utilized the Taiwan National Health Insurance Research Database. A total of 554,074 patients with dementia were compared with 554,074 age- and sex-matched patients without dementia regarding the risk of incident AF. Among patients with dementia who experienced incident AF, the risks of clinical events of patients treated with warfarin or NOACs were compared with those without OACs (reference group).Results The risk of incident AF was greater for patients with dementia compared with those without (adjusted hazard ratio [aHR]: 1.054; 95% confidence interval [CI]: 1.040–1.068 for all types of dementia, aHR: 1.035; 95% CI: 1.020–1.051 for presenile/senile dementia, and aHR: 1.125; 95% CI: 1.091–1.159 for vascular dementia). Among patients with dementia and experienced incident AF, warfarin use was associated with a higher risk of ischemic stroke (aHR: 1.290; 95% CI: 1.156–1.440), intracranial hemorrhage (ICH; aHR: 1.678; 95% CI: 1.346–2.090), and major bleeding (aHR: 1.192; 95% CI: 1.073–1.323) compared with non-OACs. NOAC use was associated with a lower risk of ischemic stroke (aHR: 0.421; 95% CI: 0.352–0.503) and composite risk of ischemic stroke or major bleeding (aHR: 0.544; 95% CI: 0.487–0.608) compared with non-OACs. These results were consistent among the patients after the propensity matching.Conclusion In this large nationwide cohort, the risk of newly diagnosed AF was higher in patients with dementia (all dementia, presenile/senile dementia, and vascular dementia) compared with those without dementia. For patients with dementia who experienced incident AF, NOAC use was associated with a better clinical outcome compared with non-OAC. Patients with dementia require a holistic approach to their care and management, including the use of NOACs to reduce the risks of clinical events.
Keywords: atrial fibrillation; dementia; NOACs